Successful Management of Peri-Implantitis around Short and Ultrashort Single-Crown Implants: A Case Series with a 3-Year Follow-Up - Lombardo, Giorgio (Int J Dent, 2019)
INTRODUCTION AND AIM: In case of peri-implantitis, resective surgery is contraindicated for short and ultrashort implants, limiting the treatment options to regenerative surgery or to implant removal. This retrospective case series presents the clinical and radiographic outcomes of a surgical regenerative procedure to treat peri-implantitis around short and ultrashort implants. MATERIALS AND METHODS: The study is a retrospective evaluation of patients suffering from peri-implantitis and those who underwent access flap surgery, concomitant chemical and mechanical decontamination of implant surface, and bone grafting using a self-hardening mixture of bone substitutes and biphasic calcium sulfate. No membranes were applied to cover the grafting material, and primary tension-free closure was achieved. The retrospective protocol was reviewed and approved by the Ethics Committee for Clinical Sperimentation (CESC) of Verona and Rovigo, Italy (based in the University of Verona) (Prog. 1863CESC. Date of approval: 2018-07-04). RESULTS: 15 patients (17 implants) have been diagnosed with peri-implantitis after a mean follow-up of 24 months after loading. Implant length was between 5 and 8 mm. 8 patients (10 implants) had a history of periodontitis. At baseline, the mean PD (probing pocket dept) at the deepest site was 8.12 mm, with an average mBI (modified bleeding index) of 2.35 and a mean BD (bone defect depth) of 3.04 mm. At the 3-year follow-up, the CSR was 100%, the mean mBI was 0.88 (average reduction: −1.47), the mean PD was 3.35 mm (mean PD reduction: 4.77 mm), and the mean bone defect was reduced by 1.74 mm, with a mean bone fill of 55%. CONCLUSIONS: The results of the present case series suggest that if accurate surface decontamination is achieved, high survival rate and good clinical and radiographic results can be obtained after 3 years. However, only the histological examination could confirm the growth of new bone in direct contact with the implant surface or if the grafted material only fills the space left by the peri-implant defect.